Management of biliary obstruction in patients with newly diagnosed alveolar echinococcosis: a Swiss retrospective cohort study (Swiss Medical Weekly, 2023)
BACKGROUND AND STUDY AIMS: Alveolar echinococcosis, an orphan zoonosis affecting the liver, is of increasing concern worldwide. Most symptomatic cases present at an advanced and inoperable stage, sometimes with biliary obstruction prompting biliary tract interventions. These are, however, associated with a high risk of infectious complications. The aim of this retrospective study was to compare the effectiveness and safety of conservative and interventional treatment approaches in patients with newly diagnosed alveolar echinococcosis and biliary obstruction.PATIENTS AND METHODS: Alveolar echinococcosis patients treated at two referral centres in Switzerland, presenting with hyperbilirubinaemia (total bilirubin >1.5 Upper Limit of Normal) at diagnosis were included, unless another underlying aetiology, i.e. common bile duct stones or decompensated cirrhosis, was identified. Patients were divided into two groups, according to whether they initially received a biliary tract intervention. The primary endpoint was normalisation of bilirubin levels within a 6-month period. Secondary endpoints included, among others, the occurrence of early and late biliary complications, the need for biliary tract interventions during follow-up and overall duration of hospital stays for treatment initiation and for biliary complications.RESULTS: 28 patients were included in this study, of whom 17 received benzimidazole therapy alone and 11 additionally received a biliary tract intervention. Baseline characteristics did not differ between groups. All but one patient in each group achieved the primary endpoint (p=0.747). Biliary tract intervention was associated with faster laboratory improvement (t1/2 1.3 vs 3.0 weeks), but also with more frequent early biliary complications (7/11 vs 1/17, p=0.002) and longer initial hospital stay (18 days vs 7 days, p=0.007).CONCLUSION: Biliary obstruction in patients with newly diagnosed alveolar echinococcosis can be treated effectively with benzimidazole therapy alone. Biliary tract intervention, on the other hand, is associated with a high complication rate and should probably be reserved for patients with insufficient response to benzimidazole therapy.